Argatroban dosing requirements in extracorporeal life support and other critically ill populations. Issue 189 (May 2020) - Dingman, J. Spencer; Smith, Zachary R.; Coba, Victor E.; Peters, Michael A.; To, Long
Abstract: Argatroban is a parenteral direct thrombin inhibitor that requires close monitoring to ensure safety and efficacy. Limited data exist to describe its effect in critically ill patients. This was a retrospective, single-center, cohort study that aimed to compare argatroban dosing requirements in those receiving extracorporeal life support (ECLS), continuous renal replacement therapy (CRRT), or neither. Organ dysfunction was assessed using a modified version of the Sequential Organ Failure Assessment (modSOFA) that incorporated the use of extracorporeal support systems. Eighty patients were included in the study ( n = 20, 20, 40 in the ECLS, CRRT, and support-free groups, respectively). The majority of patients were Child-Pugh classification B (73%). Median modSOFA scores were higher in the ECLS (16.5) and CRRT (15.5) groups than in the support-free group (7.5) ( P < .001). There was no difference in the primary outcome of first therapeutic argatroban dose between the three groups (0.5 μg/kg/min for each; IQRs 0.25–0.50, 0.11–0.50, and 0.25–0.50, respectively; P = .455). The ECLS group had the lowest mean (0.39 μg/kg/min), minimum (0.20 μg/kg/min), and final (0.43 μg/kg/min) doses. ECLS patients had more supratherapeutic aPTTs and dose changes overall, supporting the need for more frequent anticoagulation monitoring or dose reductions in this population. Total modSOFA score demonstrated a moderate inverse correlation with first therapeutic dose (dose = 0.54 – (modSOFA score × 0.012); R = −0.342, P = .002). Overall, initial argatroban doses of 0.3–0.5 μg/kg/min appear to achieve therapeutic aPTT values in the studied populations. Highlights: Patients on extracorporeal life support (ECLS) require reduced argatroban doses. Overall severity of organ dysfunction and ECLS modality may predict dosing needs. Consider lower argatroban doses in venoarterial ECLS than in venovenous ECLS. Further research should define optimal dosing strategies in critically ill patients.